2015
DOI: 10.1111/1744-9987.12343
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients and Their Ascites Who Underwent Repeated Cell‐Free and Concentrated Ascites Reinfusion Therapy

Abstract: Novel cell-free and concentrated ascites reinfusion therapy (KM-CART) is easy to use, safe and applicable for refractory ascites. We can get the full amount of ascites, filtrate, and concentrate in a short time. KM-CART can be applied as palliative care for dying patients including patients with massive malignant ascites. Some patients who underwent repeated KM-CART survived longer than those who did not repeat the therapy. The aim of this study was to identify the type of patients with ascites for whom KM-CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Biologically clean ascites were obtained by paracentesis under local anesthesia. Drainage was continued until flow stopped spontaneously or was interrupted at the physicians' judgment (32,33). We confirmed that endotoxins were not detected in the collected ascites, as it is known that CART is unable to eliminate endotoxin with filtration (34).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…Biologically clean ascites were obtained by paracentesis under local anesthesia. Drainage was continued until flow stopped spontaneously or was interrupted at the physicians' judgment (32,33). We confirmed that endotoxins were not detected in the collected ascites, as it is known that CART is unable to eliminate endotoxin with filtration (34).…”
Section: Methodssupporting
confidence: 67%
“…CART is an expensive and time-consuming method. Therefore, it is important to produce a suitable CART method and determine appropriate patients' indications for CART (26,32).…”
mentioning
confidence: 99%
“…Drainage was continued until flow stopped spontaneously or was interrupted at the physicians' discretion [4,5]. We confirmed that endotoxins were not detected in the collected ascites, as it is known that CART is unable to eliminate endotoxin with filtration [6].…”
Section: Cart Proceduressupporting
confidence: 68%
“…CART is an expensive and timeconsuming method. Therefore, it is important to produce suitable CART method and determine appropriate patient's indication of CART [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study revealed that most of the patients underwent multiple CART sessions. Maeda et al reported that total protein levels were high and prognosis was favorable in the patients who underwent ≥ 5sessions [6]. Also, long intervals between CART sessions and a good prognosis were reported in gynecologic cancer patients who had undergone chemotherapy [7].…”
Section: Discussionmentioning
confidence: 99%